THE READINESS OF NURSES IN PROVIDING PALLIATIVE CARE IN BALI - Krisnandari D, Anak Agung Istri Wulan; Sri Rahyanti, Ni Made (Journal of Islamic Nursing, 2021)
The number of palliative care increases over time. Nurses have the biggest regulations in providing palliative care, because of that the readiness of nurses is an important thing in a palliative care setting. This study aimed  to determine the readiness of nurses in providing palliative care. This research design was descriptive with cross sectional approach. There were four variables measured in this study such as knowledge, capability, willingness, and resilience of nurses in providing  palliative care. The questionnaires were used in data collection. The number of samples in this study were 375 nurses. Tthe results showed that nurses still had less and varied knowledge about palliative care (median 9; variant 6.4). In this study, it was also found that nurses had the capability (median 6; variant 5.5), willingness (median 5; variant 0.8) and resilience (median 3; variant 0.5) in providing palliative care. The readiness of nurses in providing palliative care must be well prepared to improved quality and quantity of palliative care.Keywords: Readiness, Nurses, Palliative Care